Hydration of Ordinary Portland Cements Made from Raw Mix Containing Transition Element Oxides - Kakali, G.; Tsivilis, S.; Tsialtas, A. (Cement and concrete research, 1998)
The subject of this paper is the study of the hydration process in cements made from raw mixes containing transition element oxides. The oxides used are ZrO 2, V 2O 5, Ni 2O 3, CuO, Co 2O 3, MnO, Cr 2O 3, TiO 2, MoO 3, and ZnO, and their percentage in the raw mixes is 2% w/w. The cement pastes are cured in water for 24 h, 48 h, 7 days and 28 days. Hydration rate and products are studied by means of X-ray diffraction, differential scanning calorimetry, and thermogravimetric analysis. As it is concluded, the added oxides provoke, in general, a retardation of the hydration reactions. The effect is stronger during the first 2 days and becomes negligible at 28 days. The addition of CuO strongly delays the hydration even after 28 days. Its action is related to the formation of Cu(OH) 2 during the first days of hydration.